Directors’ Legal Responsibility in Protecting Workers’ Rights - Limrogate Immanuel; Jamalum Sinambela (Ilmu Hukum Prima (IHP), 2025)
The protection of workers’ rights is an integral aspect of responsible corporate governance. In Indonesia, corporate policies enacted by company directors frequently result in labor rights violations, including unilateral termination, wage neglect, and denial of social security. This article employs a normative juridical and comparative approach to analyze the intersection of labor law and corporate law in defining both the authority and liability of directors. The findings reveal that directors carry fiduciary duties and a duty of care, which may extend to safeguarding workers as stakeholders. Nevertheless, Indonesian legislation has yet to explicitly impose such responsibilities on directors in relation to worker protection. This article therefore recommends harmonizing relevant regulations and strengthening corporate governance principles based on social justice within industrial relations.